2022
DOI: 10.1002/admi.202200085
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Implantation in Titania‐Based Plasmonic Photo‐anodes: A Review

Abstract: The metal‐oxide semiconductors exhibit remarkable optoelectronic properties and have immense implication in applications involving energy conversion, light emission, environmental remediation, etc. The presence of metal nanostructures in titanium dioxide (TiO2), zinc oxide metal‐oxide semiconductors have enhanced the photo‐activity, due to the plasmon resonances and are predominantly researched for organic and perovskite photovoltaics. Generally, the metal nanoparticle dopants are introduced by methods like sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 268 publications
(800 reference statements)
1
2
0
Order By: Relevance
“…A consistent decline in metal content with increasing radiation fluence for all thicknesses suggests that an Au thin layer was sputtered.The reduced sputtering yield of Au for a lower thickness of 2 nm, such as the one utilized here, the Au content per unit area of the substrate correspondingly reduces with fluence. 18 This conclusion of reduced sputtering yield in the current investigation is found to be strongly corroborated by the creation of Au nanostructures in the AFM study.A thickness-dependent sputtering has also been seen in the past. [32][33][34] Kumar et al 33 have observed a similar fluctuation of sputtering yield with the film thickness in LiF.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A consistent decline in metal content with increasing radiation fluence for all thicknesses suggests that an Au thin layer was sputtered.The reduced sputtering yield of Au for a lower thickness of 2 nm, such as the one utilized here, the Au content per unit area of the substrate correspondingly reduces with fluence. 18 This conclusion of reduced sputtering yield in the current investigation is found to be strongly corroborated by the creation of Au nanostructures in the AFM study.A thickness-dependent sputtering has also been seen in the past. [32][33][34] Kumar et al 33 have observed a similar fluctuation of sputtering yield with the film thickness in LiF.…”
Section: Resultssupporting
confidence: 78%
“…16 One of the standard techniques for creating noble metal NS implanted in a matrix is ion implantation, which allows for precise control over the depth distribution of the NS by carefully controlling the ion energy,ion beams, dose rate,dose, and substrate temperature. 17,18 The other advantage of using ion beam sputtering to create Au nanostructures is that it is a "bottom-up" approach that creates precise, uniform nanostructures with precise control over size, shape, and composition. Additionally, ion beam sputtering is a "dry" process that doesn't require the use of chemicals, making it more environmentally friendly than other methods.…”
mentioning
confidence: 99%
“…[3,19] On the other hand, wide bandgap semiconductor materials, such as TiO 2 , with salient performance in photo-based applications suffer from low conductivity with weak energy storage capabilities. [20,21] To mitigate this issue, alloying/doping strategies are shown to boost the material's conductivity. [3,19,22] Similarly, defect engineering is a promising protocol to tune the material's intrinsic electronic conductivity and tailor its electronic band structure.…”
Section: Introductionmentioning
confidence: 99%